EXPOSURE LEVELS OF PATIENTS DURING RADIOLOGICAL EXAMINATIONS IN ST. PETERSBURG AND THE LENINGRAD REGION - V. Yu Golikov; M. I. Balonov; S. A. Kalnizky; A. A. Bratilova; S. S. Sarycheva; I. G. Shazky; A. V. Vodovatov (Радиационная гигиена)
Saint-Petersburg Institute of Radiation Hygiene has undertaken in 2009-2010 selective regional study of exposure levels of adult patients during radiological diagnostic procedures in 20 hospitals of the city Saint-Petersburg and the Leningrad region. We examined 52 X-ray machines, 14 computed tomography rooms and 9 angiography rooms. The average effective doses, depending on the technology and type of patient examination, varied within the following limits: routine radiographic procedures - from 0.05 mSv to 0.6 mSv, computed tomography procedures - from 0.6 to 17.5 mSv, interventional examinations - from 6 to 60 mSv. The obtained effective doses of the patients in the studied hospitals of Sant-Petersburg and Leningrad region are compared with the average values recommended in the statistical form 3-DOS, and with published foreign data.